تقييم كفاءة الاداء لشركة الكندي لإنتاج اللقاحات والادوية البيطرية للمدة (2021-2022) (دراسة تقويمية و تحليلية) - الموسوي حنان عبد الخضر هاشم; جودة عماد عبد الهادي (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The vaccine and veterinary medicine industry is considered one of the important industries in the world. It also plays an important role in reviving the national economy and achieving food security for citizens by preserving livestock in any country in the world. The availability and accessibility of effective vaccines is vital and important to combat many animal diseases and prevent their spread، some of which can also spread to humans. Which causes harm and harm to society and the economy. Iraq is one of the countries that seeks to grow and protect its livestock because of its major role in achieving food security and reviving the local industry through Manufacture of vaccines and animal medicines and food industries that can contribute to the revitalization and growth of the local economy like other industries، so great importance must be given. for these industries.